Escolas de samba no Rio de Janeiro: cultura, apropriação dos desfiles e precarização no barracão - Lima, Bruno Souza Duarte (2023)
This dissertation seeks to understand culture under the domination of capital, where ways of life are exterminated or incorporated into a dominant culture conducive to capitalist development. Thus, like ways of life, cultural production is also appropriated when it can be accommodated in the market and thus transformed into a commodity, which is intensified by the birth of the cultural industry. The development of the samba schools in Rio de Janeiro is an illustrative case of the appropriation of a cultural practice driven by meanings and values distinct from those imposed by way of life enacted by capital. Based on a materialist view of culture, we try to discuss the development of the samba schools as a cultural production, an expression of black culture that was appropriated by the cultural industry, transforming itself into a marketable product. From this, we observe the changes in the work processes and labor culture in the sheds of the samba schools, engendered by commodification, contributing to the precariousness of working relations and conditions